2022
DOI: 10.1186/s13287-021-02684-0
|View full text |Cite
|
Sign up to set email alerts
|

Applications of the amniotic membrane in tissue engineering and regeneration: the hundred-year challenge

Abstract: The amniotic membrane (Amnio-M) has various applications in regenerative medicine. It acts as a highly biocompatible natural scaffold and as a source of several types of stem cells and potent growth factors. It also serves as an effective nano-reservoir for drug delivery, thanks to its high entrapment properties. Over the past century, the use of the Amnio-M in the clinic has evolved from a simple sheet for topical applications for skin and corneal repair into more advanced forms, such as micronized dehydrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 183 publications
0
61
0
1
Order By: Relevance
“… 202 Apart from placenta, decellularized amniotic membranes (the inner lining of the placenta) have also been exploited due to a rich pool of growth factors and intact BM component. 203 The group of Nasiry et al reported the successful use of microporous 3D decellularised amniotic membranes scaffold for wound healing in diabetic rats. 204 Comparable to the native ultrastructural and molecular properties, the use of human amniotic membranes as scaffolds to support porcine urothelial cells was reported by group of Jerman et al 205 Despite the ability to mimic the native tissue architecture and provision of bioactive cell adhesion sites and growth factors, the use of dECM is limited.…”
Section: Hydrogel As Bm Mimicsmentioning
confidence: 99%
See 1 more Smart Citation
“… 202 Apart from placenta, decellularized amniotic membranes (the inner lining of the placenta) have also been exploited due to a rich pool of growth factors and intact BM component. 203 The group of Nasiry et al reported the successful use of microporous 3D decellularised amniotic membranes scaffold for wound healing in diabetic rats. 204 Comparable to the native ultrastructural and molecular properties, the use of human amniotic membranes as scaffolds to support porcine urothelial cells was reported by group of Jerman et al 205 Despite the ability to mimic the native tissue architecture and provision of bioactive cell adhesion sites and growth factors, the use of dECM is limited.…”
Section: Hydrogel As Bm Mimicsmentioning
confidence: 99%
“…Similarly, porous hybrid placental-ECM sponges (PIMS), derived by combining silk fibroin and placental ECM, displayed the potential to regenerate bone tissue . Apart from placenta, decellularized amniotic membranes (the inner lining of the placenta) have also been exploited due to a rich pool of growth factors and intact BM component . The group of Nasiry et al reported the successful use of microporous 3D decellularised amniotic membranes scaffold for wound healing in diabetic rats .…”
Section: Hydrogel As Bm Mimicsmentioning
confidence: 99%
“…Biocompatibility is a signi cant issue when selecting or engineering biomaterials to circumvent adverse reactions in the host body, such as in ammation during tissue engineering [7][8][9][10][11]. Mechanical and structural properties are frequently required for tissue engineering to work well.…”
Section: Introductionmentioning
confidence: 99%
“…A poly (amidoamine) (PAMAM) dendrimer acts as a hydrophobic micro-container for encapsulating small molecules and nanoparticles in hydrophilic environments via electrostatic or hydrophobic interactions [5][6][7][8][9]. PAMAM has been studied for retarded release in LbL multilayers [10].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising biomedical applications of porous membranes is the formation of a cell sheet using membranes with micro- and nanopores for the regeneration of damaged tissues caused by diseases or accidents [ 9 , 10 , 11 , 12 , 13 ]. To supply water from a cell sheet periphery, temperature-responsive Poly(N-Isopropylacrylamide) (PIPAAm)-porous membranes (mean roughness: 4.40 nm) have been developed for complete cell sheet detachment [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%